A Review of Important Activities and Studies 1965-66 - Planning Commission (Planning Commission, 1966)
In pursuance of the suggestions of the National Development Council made at its 21st meeting held on 27th and 28th October, 1964, the sectoral programmes of development, as well as questions relating to aggregate resources for the Fourth Plan, were re-examined by the Planning Commission, after taking into account the findings of the five Sub-committees set up by the Council. As a consequence, certain alterations in the total outlay and in the sectoral allocations which had been set out in the “Memorandum on the Fourth Five Year Plan” were made. The Commission’s proposals, along with the policy decisions required for the effective implementation of the Plan, were set out in the document “Fourth Five Year Plan—Resources, Outlays and Programmes” which was submitted to the National Development Council, for its consideration, at its 22nd meeting held on 5th and 6th September, 1965.
Government of India Planning Commission